THE IMPLEMENTATION OF LEARNING STRATEGY THROUGH QUESTION STUDENT HAVE (QSH) AT VOCATIONAL SCHOOL IN BANDUNG REGENCY - Dindin Syarif Nurwahyudin; Agung Maulana (IKIP Siliwangi, 2018)
Learning Math needs stages which is in line with mental development as well as cognitive aspect. The point of view in this implication through learning math is to encourage awareness, produce questions, able to oppose, able to predict, appreciate to the own valuable invention, encourage students to find out math stucture and design, and encourage to think critically. Moreover, students are encouraged to analize with their assumption with credible sources, find out whether the sources are credible or not, identify and evaluate, try to implement some strategies to make the correct decision based on available assessment. One of learning stages which is offered is active learning strategy. One of the application is QSH (Question Student Have) strategy. With this method, the achievement and improvement of Mathematical critical thinking of vocational school students. Furthermore, students can easily solve their problems in (a) simplifying square root, (b) deciding sinus, cosinus, and Tangen angles, and (c) phytagoras concept.